Homecoming : foreign-educated returnees' experience of reentry into Chinese Universities in Yunnan Province, China : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Wellington, New Zealand - Wang, Min (Massey University, 2016)
With the growing number of foreign-educated graduates returning to China, few studies have been done on what happens when they return, especially those who work in Chinese universities. The purpose of the study is to explore the re-entry experiences of returnees who have been employed in higher education institutions in Yunnan Province, China, from three different perspectives: the perspectives of returnees, non-returnees and administrators via one-to-one interviews. The study assesses what difficulties and challenges these returnees face when they returned to China to work at Chinese academic communities and also make recommendations on how Chinese universities can make use of returnees’ social and cultural capital based on the findings of the study. In this study qualitative and quantitative research methods have been used to collect information from different sources. Qualitative method was adopted as the primary method and quantitative as supporting role. Twenty-four foreign-educated returnees and 11 non-foreign-educated graduates were interviewed. Nine management leaders were also interviewed to explore the organisational perspectives in dealing with the returnees. Simultaneously three different group questionnaires were distributed to these participants to collect quantitative data. Analysis of the data suggested that these returnees encountered challenges in re-adapting into Chinese universities, both academically and culturally, even though they were regarded as having social and cultural capital advantages. The data indicated that returnees had difficulties in utilising their knowledge in Chinese universities. They had limited influence on the universities’ research, teaching, and management or on changing the academic environment. The Chinese academic culture, the administration systems and returnees’ changing of cultural perceptions helped to influence returnees’ re-entry experiences. Among these factors, academic re-adaptation and the bureaucratic system were the two factors that influenced returnees’ experiences most. The returnees reported negative attitudes towards Chinese universities in two areas: the Chinese academic culture; the bureaucratic nature of the Chinese universities. It is argued in this study that if the Chinese government and the management levels of universities want to make use of returnees’ social and cultural capital, universities should build a healthy organisational culture and improve their services to returnees. It is critically important for Chinese universities to establish a more reasonable assessment system to guide research and teaching. Also, in a healthy academic environment, research should not be connected with bureaucratic power. That is, universities’ management systems would focus on professionalism instead of managerialism. Further, establishing a supportive management system will help returnees to re-adapt to their Chinese academic life smoothly. For returnees, it is suggested that they should hold realistic expectations towards Chinese academic and social culture in order to manage issues in re-adaptation. To deal with workplace cultural and sociocultural issues, it is important for them to communicate with colleagues and friends as often as possible, thus to help them become familiar with the cues and norms of the home culture again. Further, returnees would need to actively establish research teams that include both returnees and non-returnee colleagues. It will help them to employ their knowledge learned overseas, and at the same time, to build effective interpersonal relationships with non-returnees and other returnees.
Keywords: Returned students; College students; Reverse culture shock; Yunnan Sheng; China